Development of A Soft Skills-Based Learning Model With A Behavioristic Approach - Imron, Imron; Khambali, Khadijah Mohd; Rifai, Afga Sidiq; Nugroho, Irham (Jurnal Tarbiyatuna, 2021)
Learning in the classroom is an important aspect of transmitting soft skills to students and a behavioristic approach has promising potential to be integrated with the process. The purpose of this research was to: (1) to determine the implementation of soft skills-based learning model development; and (2) to discover the development of a soft skills-based learning model to improve soft skills in students of the Faculty of Islamic Religion, University of Muhammadiyah Magelang. Therefore, this was a classroom action research and the design used was the model developed by Kemmis and Taggart. This consisted of four components, namely, planning, action, monitoring, and reflection. Furthermore, this research used the descriptive-quantitative analysis technique and three data collection methods namely observations, interviews, and questionnaires. These results indicated that: (1) the development of a soft skills-based learning model with a behavioristic approach is performed in several stages, namely: (a) the planning stage which includes soft skills attributes, lesson plans, and learning models determination including making assessment instruments; (b) implementation stages; (2) Development of soft skill-based learning model using a highly effective behavioristic approach to improve students' soft skills. This can be observed in the acquisition of soft skills scores, which were on average 10.6 at the start of the lecture and 20.41 at the conclusion.